2020
DOI: 10.1161/strokeaha.119.027071
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Outcomes of Intravenous Thrombolysis in Posterior Versus Anterior Circulation Stroke

Abstract: Background and Purpose— Posterior circulation stroke (PCS) accounts for 5% to 19% of patients with acute stroke receiving intravenous thrombolysis. We aimed to compare safety and outcomes following intravenous thrombolysis between patients with PCS and anterior circulation stroke (ACS) and incorporate the results in a meta-analysis. Methods— We included patients in the Safe Implementation of Treatments in Stroke Thrombolysis Registry 2013 to 2017 with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
34
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 30 publications
13
34
3
Order By: Relevance
“…Atrial fibrillation was previously found more frequently in patients with ACS 5 , 8 , 9 , 15 . On the other hand, the lower incidence of diabetes in PCS contrasts with previous observations which indicated an equal prevalence of diabetes in PCS and ACS 5 , 13 , 15 , 21 , 22 , 26 , 27 or even a higher prevalence in PCS patients 7 9 , 29 . While we did not find any differences between PCS and ACS patients concerning pre-stroke medication, other studies suggest a greater use of antihypertensives 5 and platelet inhibitors in ACS 10 , 22 .…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Atrial fibrillation was previously found more frequently in patients with ACS 5 , 8 , 9 , 15 . On the other hand, the lower incidence of diabetes in PCS contrasts with previous observations which indicated an equal prevalence of diabetes in PCS and ACS 5 , 13 , 15 , 21 , 22 , 26 , 27 or even a higher prevalence in PCS patients 7 9 , 29 . While we did not find any differences between PCS and ACS patients concerning pre-stroke medication, other studies suggest a greater use of antihypertensives 5 and platelet inhibitors in ACS 10 , 22 .…”
Section: Discussioncontrasting
confidence: 93%
“…Moreover, we observed a better three months functional outcome after acute stroke therapy in PCS. Our findings are in line with a recent data analysis from the SITS-MOST (Safe Implementation of Thrombolysis in Stroke Monitoring Study) registry, which had intracerebral haemorrhage (ICH) after intravenous thrombolysis as primary outcome, and found less ICH in patients with PCS strokes, along with a higher proportion of patients reaching functional independence (mRS 0–2) at 3 months 16 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is likely explained by "ceiling effects" of the NIHSS, particularly for basilar artery occlusion, which may be associated with severe disturbance of consciousness and high NIHSS score while causing ischemia in a tissue volume less than that of a complete middle cerebral artery territory (52). Recently, the risk of sICH after IV tPA in posterior circulation strokes was found to be half of that of anterior circulation strokes, albeit with higher risk of death, which illustrates the limitations of the NIHSS score for stroke severity assessment (53).…”
Section: Stroke Severitymentioning
confidence: 99%